Community-Based Cluster of Methicillin-Resistant Staphylococcus Aureus in Manitoba - Carol A Kurbis; John L Wylie (Canadian Journal of Infectious Diseases)
A community-based, single strain cluster of methicillin-resistant Staphylococcus aureus (MRSA) is described. The cluster of cases was identified in a small rural community in southwestern Manitoba, although some spread of the MRSA strain to neighbouring communities was observed. The majority of people were otherwise healthy, had no contact with the hospital system and did not fit the profile of those at risk for MRSA infection.